2014
DOI: 10.1179/1743294414y.0000000259
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cold spray coating in industrial medical waste incinerator

Abstract: NiCrAlY coating was deposited on Ni based Superni 76 superalloy using cold spray process to enhance the life of superalloy. The present investigation is an attempt to evaluate comparative behaviour of hot corrosion of the bare and coated superalloy in actual industrial medical waste incinerator. The study was conducted in the secondary chamber of medical waste incinerator for 1000 h under cyclic conditions at 900uC. The life of bare and coated superalloy has been evaluated based on thickness lost due to erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Owing to this unique coating structure, the chlorine present on the surface deposits from the incinerator environment is noticed to be unable to start the oxychlorination reactions based active oxidation mechanism. This mechanism first reported by Miller et al 18 and is reported [1][2][3][4]7 widely for the chlorine based corrosive environment similar to incinerators (Fig. 1).…”
Section: Mechanismsupporting
confidence: 62%
See 2 more Smart Citations
“…Owing to this unique coating structure, the chlorine present on the surface deposits from the incinerator environment is noticed to be unable to start the oxychlorination reactions based active oxidation mechanism. This mechanism first reported by Miller et al 18 and is reported [1][2][3][4]7 widely for the chlorine based corrosive environment similar to incinerators (Fig. 1).…”
Section: Mechanismsupporting
confidence: 62%
“…The role of the coating is to provide a metal surface composition which reacts with the environment to produce a protective scale and block the penetration of corrosive species towards the substrate. [4][5][6] The highly dense microstructure with low open porosity, along with resistance to spallation and cracks due to thermal fluctuations and erosivity of the flue gases, is the requirement of coatings. Effective coatings also need to restrict the diffusion of substrate elements towards the exposed surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the microstructure is not good enough, then the environmental species can reach the coatingsubstrate interface. This can trigger the failure of the bonding between the coating and the substrate [13][14][15][16][17][18][19][20][21][22]. The microstructure is mainly decided by the coating deposition technique.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the minor alloying elements such as Mo, present in the coatings can support the formation of protective chromia [49], [50]. Zahs et al studied [40] the chlorine-induced high temperature corrosion of a wide range of alloys with focus on the behaviour of the alloying elements between 400-700 °C.…”
Section: Structure and Surface Morphology Of Corrosion Productsmentioning
confidence: 99%